2017
DOI: 10.1016/j.bbadis.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of sestrin2 increases pro-inflammatory reactions and ER stress in the endothelium via an AMPK dependent mechanism

Abstract: Knockdown of sesn2 aggravates atherosclerotic processes by increasing pro-inflammatory reactions and ER stress in the endothelium via an AMPK-dependent mechanism, suggesting that sesn2 might be a novel therapeutic target for atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(41 citation statements)
references
References 30 publications
0
41
0
Order By: Relevance
“…After 1 day, heart tissue was harvested. A detailed experimental design is described in our previous report [ 17 ]. This study was approved by the Institutional Animal Care and Use Committee (IACUC) of Korea University (Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After 1 day, heart tissue was harvested. A detailed experimental design is described in our previous report [ 17 ]. This study was approved by the Institutional Animal Care and Use Committee (IACUC) of Korea University (Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…Park et al [ 15 ] reported that obesity-induced hepatic endoplasmic reticulum (ER) stress and apoptosis were elevated in sesn2-deficient mice compared to normal mice. In vascular endothelial cells, inhibition of sesn2 was shown to elevate ROS production and cytotoxicity induced by inflammatory stimuli [ 16 , 17 ]. Although growing evidence suggests that sesn2 protects against various cardiometabolic diseases such as nonalcoholic fatty liver disease (NAFLD) and atherosclerosis, it is unclear whether sesn2 has a beneficial effect against cardiomyopathy-related molecular events.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was recently shown that knockdown of Sestrin2 potentiates the formation of atherosclerotic plaques and other hallmarks of atherosclerosis in mice [50]. The underlying mechanism for this effect appears to involve increased ROS production and ER stress as well as increased adhesion molecules in the vasculature [50]. Taken together, Sestrins 1 and 2 may prove to be attractive targets for amelioration of cardiovascular diseases.…”
Section: Significance Of Sestrins In Diseasesmentioning
confidence: 99%
“…Activation of AMPK can suppress inflammatory response and oxidative stress during OGD/R in H9c2 cells [28]. Importantly, accumulating evidence shows that Sesn2 can activate the AMPK pathway and further protect against a variety of conditions [29,30]. In this study, we found that the expression levels of p-AMPK and p-ACC were upregulated in the OGD/R group compared with the control group, whereas sufentanil treatment further enhanced the expression levels of the studied proteins ( Figure 5).…”
Section: Sufentanil Protected Against Myocardial I/r Injury In H9c2 Vmentioning
confidence: 99%